2007
DOI: 10.1038/nsmb1310
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and dynamics of SNAREpin folding across lipid bilayers

Abstract: Membrane fusion occurs when SNAREpins fold up between lipid bilayers. How much energy is generated during SNAREpin folding and how this energy is coupled to the fusion of apposing membranes is unknown. We have used a surface forces apparatus to determine the energetics and dynamics of SNAREpin formation and characterize the different intermediate structures sampled by cognate SNAREs in the course of their assembly. The interaction energy-versus-distance profiles of assembling SNAREpins reveal that SNARE motifs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
274
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 246 publications
(293 citation statements)
references
References 60 publications
14
274
2
3
Order By: Relevance
“…This intermediate may be transient in vivo, formed after trans-SNARE complex assembly and close to the point of fusion. Although detailed electrophysiological experiments will be needed to determine the precise role of SNARE complex dimers in membrane fusion events, one can speculate from their solution structure how they might contribute toward formation of an oligomeric complex around a fusion pore, consistent with the energies required to bring about membrane fusion (Li et al, 2007). It is interesting to note that the syb2(W89A,W90A) mutant does not seem to be defective in mediating liposomal fusion events (Siddiqui et al, 2007), whereas it profoundly inhibits Ca 2ϩ -dependent secretion.…”
Section: Discussionmentioning
confidence: 99%
“…This intermediate may be transient in vivo, formed after trans-SNARE complex assembly and close to the point of fusion. Although detailed electrophysiological experiments will be needed to determine the precise role of SNARE complex dimers in membrane fusion events, one can speculate from their solution structure how they might contribute toward formation of an oligomeric complex around a fusion pore, consistent with the energies required to bring about membrane fusion (Li et al, 2007). It is interesting to note that the syb2(W89A,W90A) mutant does not seem to be defective in mediating liposomal fusion events (Siddiqui et al, 2007), whereas it profoundly inhibits Ca 2ϩ -dependent secretion.…”
Section: Discussionmentioning
confidence: 99%
“…13, are interpreted as the total free energy required to induce stalk formation [e.g. (64)(65)(66)]. However, this value only includes bending and tilt deformations with respect to a flat monolayer of the same area.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated the sufficiency of SNAREs to mediate fusion when reconstituted into a number of model systems, including freestanding lipid vesicles (4-7), supported lipid bilayers (8)(9)(10), and tethered vesicles (11). Generally these studies suggest that SNAREs are able to bring two membranes into close apposition by forming a trans complex in a docking reaction which is highly energetically favorable (12). This is illustrated in Fig.…”
mentioning
confidence: 92%